Deviasi Taksiran Berat Janin pada Metode Johnson-Toshack, Formula Sederhana dan Formula Dare - Rianti, Emy; Aminah, Siti (Jurnal Kesehatan, 2017)
The ability of the birth attendant to estimate the birth weight of the fetus is very important that it does not cause childbirth dystocia that may cause rip in the birth canal. The aim of this study was to compare the deviation of fetal weight estimation according to Johnson-Toshack method, simple formula and Dare formula. Thedesign used was cross sectional, the data taken primarily, involving 100 respondents at Fatmawati General Hospital Jakarta, from August to September 2015. The findings showed that the smallest deviation mean of fetal weight estimation is Johnson-Toshack method. The results of this method of measurement tend to be close to infant birth weight, especially in the client childbirth with abdominal circumference 90 - 100 cm. The conclusion of this study is that Johnson-Toshack's fetal weighing estimates are more appropriate for childbirth with 90 to 100 cm abdominal circumference size, except in childbirth with ruptured membranes, applying a fetal weight estimate based on the Dare formula would be more appropriate.